Sustainability science a multidisciplinary approach - Komiyama, Hiroshi 1944-.; United Nations University. Press (Tokyo United Nations University Press, 2011)
Sustainability science is an academic discipline that emerged in response to threats to the sustainability of the global environment. Its purpose is to help build a sustainable society by developing solutions to climate change, the exhaustion of resources, ecological destruction and other environmental crises that threaten the future of humanity. Sustainability science demands a realignment of existing academic disciplines. Whereas academia has fragmented into discrete fields of in-depth specialization, sustainability science seeks comprehensive, integrated solutions to complex problems and a restructuring of education and research that spans multiple disciplines. This volume offers approaches to the development of a transdisciplinary perspective that embraces natural, social and human sciences in the quest for a sustainable society.--Publisher's description.
Introduction -- The connections between existing sciences and sustainability science -- Concepts of "sustainability" and "sustainability science" -- Tools and methods for sustainability science -- The redefinition of existing sciences in light of sustainability science -- Education -- Conclusion.
Includes bibliographical references and index.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Sustainable development -- Research